Motivation in Times of Change: Women and Educational Professions - Risa R. Simanjuntak (Bina Nusantara University, 2010)
Motivation is a complex issue, in which theorists have tried to approach. Among the classifications are content theories, process theories and integrated theories. Women’s world is also complex, where multiple roles involve motivations and lead to different actions. This makes women perfect examples for management in times of change. Article discusses examples of motivation and management in times of change. Subjects of this study primarily are women lecturers and middle managers in educational field of professions. This study also involves qualitative means of data collection with two questions to lead discussions: What has driven you to be lecturers/educators?; What will make you continue become lecturers/educators? Analysis were conducted based on the studies done by Coleman, Ninomiya & Okato,and. Mwamwenda. It is concluded that women have multiple rather than single factors to motivate them in the profession. It is also agreed that leaders with feminine qualities as well as sensitive to culture are more preferable than those who are absent with them.